2017
DOI: 10.1515/ausm-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

New characterization of symmetric groups of prime degree

Abstract: Abstract. In this paper, will show that a symmetric group of prime degree p ≥ 5 is recognizable by its order and a special conjugacy class size of (p − 1)!.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Similar characterizations have been found in [5], [2] , [8], [6], [7] and [5] for the groups: PSL(n, 2), 2 D n (2), 2 D n+1 (2), C n (2) , alternating group of degree p, p + 1, p + 2 and symmetric group of degree p, where p is a prime number.…”
Section: Introductionsupporting
confidence: 77%
“…Similar characterizations have been found in [5], [2] , [8], [6], [7] and [5] for the groups: PSL(n, 2), 2 D n (2), 2 D n+1 (2), C n (2) , alternating group of degree p, p + 1, p + 2 and symmetric group of degree p, where p is a prime number.…”
Section: Introductionsupporting
confidence: 77%
“…Asboei and Mohammadyari used the group order and just one special conjugacy class size to verify Thompson's conjecture for alternating simple groups of degrees p, p + 1 and p + 2, where p is a prime number, see [3] and [4]. They also extended their result to symmetric groups of prime degrees, see [5]. Furthermore, Asboei et al in [2] recently showed that simple symplectic groups PSp 2n (2) are determined uniquely up to isomorphism by their order and one conjugacy class of size |PSp 2n (2)|/(2 n + 1).…”
Section: Introduction and Main Resultsmentioning
confidence: 96%